Analysis of candidate genes ZEB1 and LOXHD1 in late-onset Fuchs' endothelial corneal dystrophy in an Indian cohort. (4th July 2018) - Rao, Bhavna S.; Ansar, Samdani; Arokiasamy, Tharigopala; Sudhir, Rachapalli R.; Umashankar, Vetrivel; Rajagopal, Rama; Soumittra, Nagasamy
ABSTRACT: Background : Fuchs' endothelial corneal dystrophy (FECD) is a complex degenerative disease of the corneal endothelium with genetic predisposition. Pathogenic rare variants have been identified in SLC4A11, LOXHD1, ZEB1, and AGBL1 . Association of single nucleotide polymorphisms (SNPs) and CTG trinucleotide repeat expansions in the intron of TCF4 gene to FECD has been studied across multiple ethnicities. Recently, genome-wide association studies have also identified KANK4, LAMC1, and ATP1B1 as novel loci for FECD. Here, we report the contribution of ZEB1 and LOXHD1 genes in our sporadic late-onset FECD cohort. Materials and methods : In the experimental study, coding regions of ZEB1 and LOXHD1 were screened by Sanger DNA sequencing in 52 late-onset and 5 early-onset FECD cases of Indian origin, recruited at a tertiary eye care center. Further, bioinformatics analysis was done. Results : One reported missense mutation, c.2522A>C; p.(Q841P), and one variant of uncertain significance (VUS), c.619A>G; p.(S207G), were identified in the ZEB1 gene. One VUS, c.6413G>Ap.(R2138Q), was observed in LOXHD1 . A 3D structural bioinformatic analysis of the missense variant in LOXHD1 predicted the variant to affect the structure–function relationship of the protein. Discussion : While mutations in ZEB1 contributed to 2% of the late-onset FECD cases, the exact role of the two VUS identified in ZEB1 and LOXHD1 in FECD pathogenesis needs to be studied.